Finite element analysis of hip implant using additive manufacturing materials in different loading conditions - Noman, Abdulla All; Mohd Shamil, Shaari; Mohd Akramin, Mohd Romlay; Tan, Kim Seah (Faculty Mechanical Engineering, UMP, 2025)
A hip implant is a crucial medical device designed to restore mobility and relieve pain for an individual with a hip joint with degenerative diseases or injury. Conventional manufacturing techniques have limitations in producing personalized implants. In contrast, additive manufacturing (AM) offers a solution by enabling the production of hip implants using biocompatible materials, such as Ti-alloy, CoCr-alloy, and Mg-alloy. Ti alloys are used for their superior biocompatibility and mechanical performance. This study aims to utilize a computer-aided design file in finite element analysis (FEA) to predict implant stress distribution, deformation, and potential biomechanical performance. The methodology includes designing the hip implant with CAD software and using Ansys to assess the mechanical performance of hip implants using Ti-6Al-4V, an AM material, at four different loading conditions. The results indicate that the total deformation at four different loadings is as follows: sitting, 0.15%; standing, 0.17 mm; walking, 0.21%; and jogging, 0.33%. The equivalent von Mises stresses of the hip implant while sitting: 288.83 MPa, standing: 339.8 MPa, walking: 423.73 MPa, and jogging: 650.93 MPa. Additional analysis of shear stresses for the hip implant while sitting: 59.738 MPa, standing: 70.28 MPa, walking: 84.556 MPa, and jogging: 134.630 MPa. Based on the result, maximum deformation, equivalent stress, and shear stress are predicted to be highest while jogging compared to other activities due to the highest load acting on the hip implant, and equivalent stresses are less than the material’s yield strength and similarly shear stresses are less than the material’s shear strength that indicates the design is safe under physiological loadings. In conclusion, this study successfully implemented the FEA of hip implants using AM materials to achieve potential mechanical performance. The integration of AM and FEA holds promise for the future of modern hip replacement surgery.